Sistema de gerenciamento de energia para controle de carga/descarga entre baterias de lítio e ultracapacitores, envolvendo sistema de tração elétrica com frenagem regenerativa - Ferreira, Tarcísio José Pedrobon [UNESP] (2014)
With the batteries’ technology evolution, the automobile industries noted the vehicle’s promising potential and comes strongly investing in passenger cars, offering the hybrid electric vehicles (liquid and electricity fuels), attracting the more conservative public, besides working on the evolution of automotive electrical systems. With prospects of a not too distant future in Brazil, this work is the development of energy management system between a battery and a supercapacitor packs, including regenerative breaking process. The electrical energy conditioning topology adopted is the cascaded configuration of two bidirectional DC- DC converters, which provide the energy power flow between energy storage components aforementioned and the vehicle traction machine. The regenerated energy, drawn from the traction machine in generator mode, is stored in the power conditioners, where the power flux depends on the charge condition of each one of the conditioners. For the control logic development, the storage system characteristics and the conditioners power transfer capacity are considered, once a hybrid energy storage system (batteries/supercapacitors) is used, taking into account the advantages of each technology. For simulation analysis and control logic management system, the Matlab/Simulink ® software was chosen because its integration to the DSpace ® platform and implementation easiness. The practical results involve a small-scale prototype, covering a programmable energy management logic, with the advantage of allowing the flexibility of new management roles implementation through programming functions